JURIDICAL ANALYSIS OF THE ROLE OF BANKING IN PREVENTING MONEY LAUNDERING CRIMES - Yasmine, Inge; Markoni, Markoni; Machmud, Aris (Jurnal Hukum Replik, 2024)
Banks, recognized as trusted institutions mandated to mediate financial transactions by collecting and channeling funds, are legally authorized entities obligated to operate with utmost diligence to thwart suspicious transactions susceptible to exploitation for illicit activities, particularly money laundering crimes. This research endeavors to explore the pivotal role of banks in Indonesia in combating money laundering. Employing a normative legal research methodology with a statutory approach, the study investigates the mechanisms employed by banks to prevent money laundering. The findings underscore that banks effectively deter money laundering practices through the implementation of robust know your customer (KYC) protocols and adherence to anti-money laundering (AML) principles as prescribed by pertinent regulationsKeywords: Know your customer (KYC) principle, banking, money laundering prevention